1998
DOI: 10.1097/00004728-199805000-00003
|View full text |Cite
|
Sign up to set email alerts
|

CT of Neural Plexus Invasion in Common Bile Duct Carcinoma

Abstract: The location and spread of neural plexus invasion in common bile duct carcinoma are characteristic and can be diagnosed by CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…CT has been used to study the extrapancreatic neural plexus invasion in common bile duct carcinoma [8,24,25] and pancreatic carcinoma [26] . �iura [24] reported that a mass-like lesion located between the medial portion of the uncinate process and the ��A or celiac artery could diagnose extrapancreatic neural plexus invasion around the SMA and celiac artery with an accuracy of 63% on CT using 5 mm slice table incremental CE-CT, when performed on eight patients with pancreatic head carcinoma.…”
Section: Carcinoma Invading Extrapancreatic Neural Plexusmentioning
confidence: 99%
“…CT has been used to study the extrapancreatic neural plexus invasion in common bile duct carcinoma [8,24,25] and pancreatic carcinoma [26] . �iura [24] reported that a mass-like lesion located between the medial portion of the uncinate process and the ��A or celiac artery could diagnose extrapancreatic neural plexus invasion around the SMA and celiac artery with an accuracy of 63% on CT using 5 mm slice table incremental CE-CT, when performed on eight patients with pancreatic head carcinoma.…”
Section: Carcinoma Invading Extrapancreatic Neural Plexusmentioning
confidence: 99%
“…Although dynamic CT is useful in assessing liver metastases and paraaortic lymph node metastases, it cannot sufficiently demonstrate tumor extent in the hepatoduodenal ligament. 20 Fukuda et al 21 reported, in an interesting article, that dynamic CT was useful for the assessment of neural invasion in common bile duct carcinoma. Although angiography can be used to assess tumor invasion to the portal vein and the hepatic artery, its diagnostic capacity is inadequate because it cannot demonstrate the tumor and the vessel simultaneously.…”
Section: Accurate Differentiation Of Benign and Malignant Biliary Stementioning
confidence: 99%
“…c Microscopic photograph of the CBD mass infiltrating the pancreas (white arrows) and the peripancreatic fat (small arrows). d High-power field microscopic photograph of the direct infiltration of adenocarcinoma (arrow) to the peripancreatic fat Pancreaticobiliary malignancies commonly invade the retroperitoneal tissues including the extrapancreatic nerve plexus which has gained importance in malignancies because it is believed to be the cause of recurrence after surgical intervention [9,10,24]. Both second portion of the extrapancreatic nerve plexus and small bowel mesentery invasion are therefore important factors that affect surgical strategy and prognosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Both second portion of the extrapancreatic nerve plexus and small bowel mesentery invasion are therefore important factors that affect surgical strategy and prognosis [25]. In a recent publication by Fukuda et al neural invasion in distal bile duct carcinoma has tendency to extend along the pancreatic plexus and presents as an irregular mass or an area of increased attenuation of retroperitoneal fat adjacent to the medial aspect of the uncinate process on CT, and as the tumor grows, neural invasion spreads medially toward the superior mesenteric artery or celiac axis, giving the vessel a thickened appearance [10]. The CT findings of infiltration of periarterial fat around the celiac and superior mesenteric arteries are said to be reliable for predicting surgical resectability while lymphadenopathy and infiltration of nonperivascular fat planes were less reliable predictors of unresectability [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation